1980
DOI: 10.1056/nejm198001173020302
|View full text |Cite
|
Sign up to set email alerts
|

Antiemetics in Patients Receiving Chemotherapy for Cancer

Abstract: Delta-9-tetrahydrocannabinol (THC) is an effective antiemetic as compared with placebos in patients receiving chemotherapy for cancer. In this study we compared THC with prochlorperazine (compazine) in a randomized, double-blind, crossover trial with patients who had failed to benefit from standard antiemetic therapy. Regardless of the emetic activity of the chemotherapeutic agents, there were more complete responses to THC courses (in 36 of 79 courses) than to prochlorperazine (in 16 of 78 courses). Of 25 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…One hour prior to the ingestion of the test meal, either the drug, THC, or a visually identical placebo was administered to each subject in a double‐blind randomized manner. The dose of THC administered to the subjects was 10 mg/m 2 of the body surface area, a dose often used in studies addressing the effectiveness of THC in prevention of chemotherapy‐induced nausea and vomiting 3 , . 7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hour prior to the ingestion of the test meal, either the drug, THC, or a visually identical placebo was administered to each subject in a double‐blind randomized manner. The dose of THC administered to the subjects was 10 mg/m 2 of the body surface area, a dose often used in studies addressing the effectiveness of THC in prevention of chemotherapy‐induced nausea and vomiting 3 , . 7 …”
Section: Methodsmentioning
confidence: 99%
“…It is an effective agent in the prevention of chemotherapy‐induced nausea and vomiting 1 . It has been shown to be superior to conventional anti‐emetic agents such as prochlorperazine in numerous controlled studies 2 –4 . Metoclopramide, a dopamine antagonist, is also effective as an anti‐emetic agent in this setting 5 .…”
Section: Introductionmentioning
confidence: 99%
“…prevention of chemotherapeutically induced nausea and vomiting [7], and other, more effective agents and combinations are being sought. In addition to the phenothiazine derivatives [8], a number of other agents or their derivatives have been studied, including: trimethobenzamide [9], dimenhydrinate [5], benzquinamide [6,10], tetrahydrocannabinol [11 13], nabilone [14], metoclopramidc [15,16], halopcridol [17,18], droperidol [19], pyridoxine [6], and various gluco corticoids [20 22],…”
mentioning
confidence: 99%
“…Table 1 shows some of the clinical trials obtained using A'-THC compared to other well-known drugs. A'-THC has been shown, to be superior in its anti-emetic effectiveness than either placebo or chlorperazine (Orr et al, 1980;Herman et al, 1979;Lucas and Lazlo, 1980;Frytak et al, 1979;Sallan et al, 1980). Sallan et al (1980) observed that younger patients, 20 years of age or less, were more likely to experience a complete anti-emetic response with THC than older patients.…”
Section: Anti-emetic Actionsmentioning
confidence: 99%
“…Various side effects were experienced by subjects ranging from psychological 'high' (Lucas and Lazlo, 1980;Orr et al, 1980;Sallan et al, 1980;Chang et al, 1979) to sedation, somnolence, orthostatic hypotension, increased heart rate, and dysphoria (Chang et al, 1979;Sallan et al, 1975). Frytak et al (1979) observed that patients suffered from blurred vision, depression, visual hallucination, nightmares, amnesia, mental confusion and fainting.…”
Section: ~~mentioning
confidence: 99%